Zn(OTf)2-Catalyzed 1,6-Conjugate Addition of Benzoxazinones to p-Quinone Methides: Access to 3,3-Diaryl-2-(2-oxo-2H-1,4-benzoxazin-3-yl)propanoic Acid Esters - Dua, Neha; Ghosh, Sonali; Peddinti, Rama Krishna (Synlett, 2021)
An effective method for the synthesis of 3,3-diaryl-2-(2-oxo-2H-1,4-benzoxazin-3-yl)propanoic acid esters is reported. A novel zinc triflate-catalyzed regioselective 1,6-conjugate addition of vinylogous carbamates to p-quinone methides for accessing the title compounds has been developed. This protocol furnished the hybrid compounds in good to excellent yields. The reaction is rapid and has a broad substrate scope.
Keywords: para-quinone methides; vinylogous carbamates; 1,6-addition; regioselectivity; diastereoselectivity; benzoxazines